Evolution and trends of artificial intelligence related to medical devices: a bibliometric analysis - Ferreira, Vasco Calixto Coelho (2024)
This bibliometric analysis critically examines the integration of artificial intelligence (AI) in medical devices, focusing on its developmental structure, prevalent research themes, and evolutionary trends. The study categorizes the research into three distinct areas: the underlying knowledge framework of AI applications in medical devices, the thematic focus of current investigations, and the chronological progression of these themes. Findings indicate a significant expansion in AI utilization, which enhances diagnostic precision and personalizes treatment modalities. The study underscores the necessity for continuous technological advancement and stringent ethical standards, proposing a roadmap for future research and practical implementation in the MedTech industry.